ANALISA RUTE DISTRIBUSI DAN BIAYA TRANSPORTASI SEBAGAI PENDUKUNG BISNIS PT POS INDONESIA KP BANJARNEGARA - Aditia Sovia Pramudita (LPPM Universitas Buana Perjuangan Karawang, 2020)
PT Pos Indonesia is a state-owned enterprise engaged in courier service inIndonesia. To achieve the competitive advantage, PT Pos Indonesia certainly cannot beseparated from its effectiveness and its efficiency in distributing letters and packages tothe customers. This research is the background of the product distribution process atPT Pos Indonesia Regional VI Semarang which based on Pos Indonesia way, where theneed for savings in needed. Therefore, the PROSAN section needs to make savings interms of distribution routes and distance. The purpose of this study is to determine thedistribution route of Pos Banjarnegara in order to minimize transportation costs. Thisresearch uses the VRP method. In this thesis, the VRP model is needed for theBanjarnegara Pos office distribution route, the solving for this method is to use savingmatrix, nearest insertion, nearest neighbor and finding out the most effective VRPsolving among those methods. Based on the calculation to complete the VRP using thesaving matrix method, the total distance is 204,3 km, the nearest insertion is 203,9, andthe nearest neighbor produces a distance of 180,6 km while the current average for thedistance in this company is 244,8 km. This shows that the nearest neighbor method ismore efficient in determining distribution routes, and this route can be done by usingjust one vehicle.Keywords: saving matrix, nearest insertion, nearest neighbor, distribution, routes